Conversational competence in english as a second language : a study of pragmatic markers - Corsetti, Cristiane Ruzicki (2015)
Conversation is one of the most fundamental activities in verbal communication. When people engage in conversational exchanges, they transmit information, perform actions, establish and maintain social relationships, among other acts. Conversation is often unplanned, takes place in real time and involves reciprocity. This thesis presents the foundations of Discourse Analysis, Pragmatics and Conversation Analysis and details discourse, pragmatic and interactional phenomena which seem to be intertwined during face-to-face conversations. It then focuses on the second language learner by addressing Interlanguage Pragmatics and by critically revisiting communicative competence frameworks and definitions of conversational competence. It justifies and proposes a conversational competence model in L2 within a pragmatic domain, comprising three facets: the management of discourse, the negotiation of illocutionary meaning and the deployment of conversational practices. It includes corpus-based investigations of pragmatic markers which are prototypical of the proposed facets of conversational competence. A small specialised corpus of Brazilian learners´ oral production at CEFR B1 had been previously built for the purposes of this thesis. Spoken sub-corpora derived from The BNC Sampler and The Diachronic Corpus of Present-Day Spoken English were selected as British English benchmark corpora. The empirical chapters of this thesis examined the most common discourse marking adverbs used to mediate segments of discourse in conversations, the most common explicit and implicit adverbial hedges used to mitigate representative speech acts and the most common minimal response tokens used to express good listenership. The pragmatic markers chosen for investigation were well , really , actually , maybe , probably , just , yeah and uhuh . It was concluded that the subjects of this study would benefit from pedagogical assistance for the acquisition of discourse markers in general, for the pragmatic functions of the adjuster just and for more varied forms to express good listenership. The markers really and yeah were employed, in their discourse and pragmatic functions, with adequate relative frequencies by the Brazilian learners. The adverb maybe was overused, signalling a tendency to use adverbial forms to express epistemic stance instead of modal verbs.